A question of definition: feminist legal scholarship, socio-legal studies and debate about law and politics - Murphy, Thérèse; Whitty, Noel (SLS Legal Publications, 2006)
In recent years, debate about the relationship between law and politics appears to have become a good deal more intense in the United Kingdom. As others have observed, one major catalyst for this has been the ascent of human rights in the popular imagination and in national, and international, legal and political orders. The problem, however, is that this development also has the capacity to skew the debate: it threatens not just the already-weakened claim that `law is politics' but also, if left unchecked, it could deepen the neglect of two questions that ought to be at the heart of debate about law and politics: namely, the question of law, and the question of the political.